The underground - Applegate, Katherine (New York : Scholastic, 1998)
The Animorphs, a group of young people who have been given the power to change into animals in order to fight an invasion by the alien Yeerks, discover a new weapon against the aliens, but it means another trip to the Yeerk pool.
"An Apple paperback.".
Christian Library.
3.9
3-6
Keywords: Extraterrestrial beings -- Fiction; Science fiction; Extraterrestrial beings -- Fiction; Science fiction